(untitled) (Prilozi za književnost, jezik, istoriju i folklor, 2023)
The article is dedicated to the influence of valide sultans on their sons and rulers of the Ottoman Empire, bearing in mind the importance of their positions. Valide sultan was the title held by the „legal mother” of a ruling Sultan of the Ottoman Empire. Тhis title was held by the living mother of a reigning sultan. But if mothers died before their sons’ accession to the throne, they were never bestowed with the title of valide sultan. Valide sultan was perhaps the most important position in the Ottoman Empire after the sultan himself. According to the Muslim tradition, saying that Мother’s right is God’s right, as mother to the sultan, the valide sultan had a significant influence on the affairs of the empire. One of the illustrations of her great power in the court was the fact that her own rooms were always adjacent to her son’s. We were especially focused on the reign of sultan Mahmud II and his life story full of different suspicion, including the clime of the honorable monk from the Atos, elder hadzi Georgiou, that Mahmud II was a crypto Christian.